The role of academic major and academic year for self-determined motivation in cooperative education. Issue 5 (October 2019) - Wild, Steffen; Neef, Christoph
Using self-determination theory, this research explores the characteristics of the basic needs of autonomy, competence and relatedness at the Baden-Wuerttemberg Cooperative State University, one of the largest institutions for cooperative education in Germany. By comparing the results from two different academic majors and two academic years, the authors examined different cultures at the university. They collected data from 426 students in a cross-sectional study. Using an analysis of variance approach (repeated-measures designs), the results show differences between relatedness with the highest characteristic values and the two other basic needs. Multivariate analysis of variance shows the significant effect of academic majors (partial η 2 = 0.10) and academic years (partial η 2 = 0.05) on all basic needs. The results are discussed in the context of different academic cultural backgrounds. Recommendations are made for improving teaching and curricula in the field of cooperative higher education.